Pengaruh Edukasi Interaktif Terhadap Pengetahuan Ibu Pada Kejadian Stunting Di Desa Ikhwan Kecamatan Dumoga Barat - Lampah, Jordan Kevin; Simak, Valen F.; Rompas, Sefti S. J. (Mapalus Nursing Science Journal, 2023)
Background: in this study is stunting in toddlers which causes toddlers to have a level of intelligence that is not maximized, children become more susceptible to disease and in the future can risk a decrease in productivity levels. Objectives: the study was to determine the effect of interactive education on maternal knowledge on the incidence of stunting in Ikhwan Village, West Dumoga sub-district. The research method used Quasi Experimental research method (pseudo experiment). The sample size was 31 respondents. Research results: from the results of the Wilcoxon statistical test on knowledge, a significant p-value of 0.035 <α so that Ho is rejected, thus, there is an influence on knowledge before and after interactive education for mothers in Ikhwan Village, West Dumoga District. Discussion: there was an increase in the mother's knowledge after interactive education ` and Conclusion: There is a significant influence between interactive education and mother's knowledge in Ikhwan village.